1994
DOI: 10.1246/cl.1994.303
|View full text |Cite
|
Sign up to set email alerts
|

Induced Assembly of Aromatic Rings Caused by a CH···π Interaction

Abstract: The bis-(N-pyridoxy-l-phenylalaninato)cobalt(III) complex exhibiting an anomalous assembly of aromatic rings around the pyridoxy 2′-methyl group has been synthesized and characterized by 1H-NMR spectroscopy and X-ray analysis. The 1H-NMR spectrum of the complex in D2O, methanol-d4 and dimethylsulfoxide-d6 revealed peculiar upfield shift in 2′-methyl group. The detailed examination of the crystal structure demonstrated that the two C–H bond vectors of 2′-methyl group were directed toward the planes of the pyrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As was previously reported, we succeeded in accurate determination of the crystal structure of the complex Na[Co(pf ) 2 ] 2. 19 It revealed that two of the three C᎐H bond vectors of the 2-methyl group were directed in the planes of the pyridoxy pyridine and phenylalanyl benzene rings of the neighbouring ligand (Fig. 6).…”
Section: Discussion Ch ؒ ؒ ؒ Interaction In Solution and Solid Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…As was previously reported, we succeeded in accurate determination of the crystal structure of the complex Na[Co(pf ) 2 ] 2. 19 It revealed that two of the three C᎐H bond vectors of the 2-methyl group were directed in the planes of the pyridoxy pyridine and phenylalanyl benzene rings of the neighbouring ligand (Fig. 6).…”
Section: Discussion Ch ؒ ؒ ؒ Interaction In Solution and Solid Statesmentioning
confidence: 99%
“…Previously, in the complexation of N-pyridoxy-phenylalanine † with Co III we suggested that the pyridoxy 2methyl group causes an inductive CH ؒ ؒ ؒ π interaction with both of pyridoxy pyridine and phenylalanyl benzene rings. 19 The N-pyridoxy--amino acid is a derivative of vitamin B 6 coenzyme, pyridoxal 5-phosphate, which plays an important role in amino acid metabolism, and the biological significance of the functional groups of the pyridoxal, i.e. pyridyl 1-N, 3-O and 4-azomethine in its metabolic intermediate, and 5phosphate ester, has long been discussed by many chemists, biochemists, and biologists.…”
mentioning
confidence: 99%
“…9). 103 They also found the indispensable role of intramolecular CH/p bonding in ternary metal complexes involving methyl-substituted phenylalanines as ligand. 104…”
Section: Interligand Interactions In Metal Compoundsmentioning
confidence: 99%
“…Synthesis and binding of simple neocarzinostatin chromophore analogues to the apoprotein 203 Analogues of neocarzinostatin have been found to bind to the apoprotein with high affinity Induced assembly of aromatic rings caused by a CH-p interaction 204 A CH-p hydrogen bond was reported to stabilise a pyridoxal analogue Lipase-catalyzed esterification of 2-(4-substituted phenoxy)propionic acids in organic solvents: substituent effect controlling enantioselectivity toward racemic acids 205 A CH-p hydrogen bond has been shown to play a role in lipasecatalyzed esterification reaction Enzymatic properties of phenylalanine 101 mutant enzyme of ribonuclease Rh from Rhizopus niveus 206 CH-p interaction has been shown to be important in enhancing the ezymatic activity Three-dimensional structure of cyanobacterial photosystem I at 2.5 Å resolution 207 Thermophilic cyanobacterium Structural information on the proteins and cofactors and their interactions has provided a basis for how the high efficiency of photosystem I in light capturing and electron transfer is achieved How does lipase flexibility affect its enantioselectivity in organic solvents? Role of CHÁ Á Áp association in stabilization of enzyme-substrate complex 208 The CH-p association between amino acids side chains around the lipase's active site was assumed to accelerate accommodation of the substrate into the enzyme CH-p interactions involving aromatic amino acids: refinement of the CHARMM tryptophan force field 209 The MP2/cc-pVTZ level calculation was applied to investigate CH-p interactions between ethene or cis-2-butene and benzene in a variety of orientations Design of artificial metalloenzymes using non-covalent insertion of a metal complex into a protein scaffold 210 The catalytic reactivity has been shown to be improved, by molecular design of the composites based on their crystal structures A circular loop of the 16-residue repeating units in ice nucleation protein 211 Tandem repeat: circular loop; aromatic ring Crystal structures of Lymnaea stagnalis AChBP in complex with neonicotinoid insecticides imidacloprid and clothianidin 212 Comparisons of the binding affinities of two complexes of AChBP gave results consistent with a role played by CH-p hydrogen bonds Critical contribution of aromatic rings to specific recognition of polyether rings 213 Crystal structure, surface plasmon resonance analyses indicated that E. coli-expressed variable domain fragments of 1C49 had the high affinity constants N-Domain of human adhesion/growth-regulatory galectin-9: preference for distinct conformers and non-sialylated N-glycans and detection of ligandinduced structural changes in crystal and solution 214 Crystallography; NMR; Near-UV CD spectroscopy Characterization of molecular recognition of STAT3 SH2 domain inhibitors through molecular simulation 215 A CH-p hydrogen bond was suggested to be responsible for some pTyr peptides binding to their corresponding SH2 domains by molecular docking and MD simulation Insight into mechanism of small molecule inhibitors of the MDM2-p53 interaction: molecular dynamics simulation and free ene...…”
Section: Titlementioning
confidence: 99%